2012
DOI: 10.1103/physreva.86.013806
|View full text |Cite
|
Sign up to set email alerts
|

Controllable enhanced dragging of light in ultradispersive media

Abstract: We have theoretically demonstrated an enhanced Fizeau effect due to dragging the light that occurs when the group velocity of light is ultraslow. The proposed experiment can be done in a cell of atomic Rb vapor under conditions such that the group velocity of light is of the order of a few hundred meters per second. We show theoretically that higher-order dispersion can influence the Fizeau effect and can be observed experimentally. It has been shown that the change of phase is sensitive to the motion of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…2 . Substituting equations (11)(12)(13)(14) into equations (8-10)) the equations of motion for the mechanical oscillator and cavity field in the frame of reference co-rotating with rotating table are given as…”
Section: Rotation Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 . Substituting equations (11)(12)(13)(14) into equations (8-10)) the equations of motion for the mechanical oscillator and cavity field in the frame of reference co-rotating with rotating table are given as…”
Section: Rotation Detectionmentioning
confidence: 99%
“…Hence, a very sensitive force detector can potentially be used as a rotation detector. In our previous work [13], Coriolis force induced displacements are measured using enhanced longitudinal Fizeau drag effect [14] to detect the rotation. In this paper, we propose a rotation detector based on the effects of the Coriolis force on the optomechanical cavity placed on a rotating table.…”
Section: Introductionmentioning
confidence: 99%
“…This effect can be used to control the group velocity of laser pulses in a slow-light medium [22,23]. It has also been shown theoretically that the light drag effect can be significantly enhanced using a slow-light material [24,25]. Moreover, a recent experiment demonstrated that spinning a slow-light material enhances the image rotation induced by rotary photon drag effect [26].…”
mentioning
confidence: 98%
“…Therefore, one can enhance the observed effect by an even larger factor, which could enable accurate detection of extremely slow speeds [24]. Note, however, that for very large group indices one has to keep higher order corrections in Eq.…”
mentioning
confidence: 99%
“…While most of the applications utilize stationary vapor cells, the recent demonstration of measuring the motion of a moving atomic vapor cell displays a way of applying an atomic vapor cell as a mo- tional sensor [11]. Here, we exploit quantum interference in electromagnetically induced transparency (EIT) effect for a moving Doppler-broadened atomic vapor cell and determine the velocity of the vapor cell by measuring the phase shift of light passing through the moving medium [11][12][13][14]. We demonstrate the sensitivity of the velocity of the atomic vapor to the level of 31 µm s −1 after 32 ms of integration time or equivalently 5.5 µm s −1 Hz −1/2 for short integration times.…”
mentioning
confidence: 99%